The Influence of Think-Pair-Share in Enhancing Students’ Speaking Ability - Hidayana Putri; Fahriany Fahriany; Nasifuddin Jalil (STKIP Singkawang, 2020)
Secondary schools obliged the students to master English skills. In fact, students have many shortcomings in mastering those English skills, especially speaking skills faced by the eighth-grade students of MTs Khazanah Kebajikan in the academic year 2017/2018. They had difficulties in speaking English directly. It was found by our observation in which the students were lack of vocabulary, self-confidence, and motivation. Additionally, they were difficult to elaborate on their ideas through the spoken form. Hence, the students are needed the new strategy to construct their shortcomings by the implementation of Think-Pair-Share. The objective of the study was to know the influence of Think-Pair-Share on students’ speaking ability of short monologue. This study used a quantitative method with a quasi-experimental design. The population was 102 students with 50 students as the sample of this study. The technique of data collection in this study consisted of pre-test and post-test. The data analysis techniques were used t-test, also included the test of normality and homogeneity. In addition, this study was also supported by measuring the effect size. The result of the study showed that students’ speaking score in the experimental class was higher than the controlled class. It found that H0 (Null Hypothesis) is rejected and Ha (Alternative Hypothesis) is accepted. Also, the result of the effect size was 2.91 at a large level (significant). It can be concluded that Think-Pair-Share is an effective way to improve students’ speaking ability, especially in short monologue.